Administrative reform in Кazakhstan: issues, trends and prospects (Journal of Philosophy Culture and Political Science, 2018)
Modern Kazakhstan successfully overcome the diffi culties of the transit period, sets new goals to furtherintegration into the world economy, increasing the country’s competitiveness and improve quality of lifein Kazakhstan. In these circumstances, the issues related to the administrative reform as the most importantfactor ensuring commitment of our society democratization and further economic growth. It should be notedthat the success of administrative reform is ensure effi cient activities of public administration. At all times, theadministrative reform is associated with greater risks and experiencing signifi cant internal resistance. Basicprinciples and directions of the administrative reform were formulated on the basis of common strategic goal ofbuilding a democratic state.Key words: administrative reform, public administration, modernization, managerial model,reforming process.